2018
DOI: 10.1038/s41586-018-0758-y
|View full text |Cite
|
Sign up to set email alerts
|

CDK12 regulates DNA repair genes by suppressing intronic polyadenylation

Abstract: Mutations that attenuate homologous recombination (HR) repair promote tumorigenesis and sensitize cells to chemotherapeutics that cause replication fork collapse, a phenotype known as “BRCAness.” 1 BRCAness tumors arise from loss-of-function mutations in 22 genes. 1 Of these genes, all but one (Cdk12) directly function in the HR repair pathway. 1 Cdk12 phosphorylates Serine 2 of the RNA Polymerase II (RNAPII) C-terminal domain (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
224
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(264 citation statements)
references
References 54 publications
13
224
2
1
Order By: Relevance
“…Notably, in the majority of cases these upstream PAS were not found in annotated 3 0 UTRs but in other exons or introns. Recently, it was reported that CDK12 suppresses intronic polyadenylation sites [63]. While our data show up-regulation of intronic PAS, considering the much larger number of potential intronic PAS compared to exonic/UTR PAS, no particular enrichment of intronic PAS was observed among upstream up-regulated PAS.…”
Section: See Materials and Methods)contrasting
confidence: 71%
“…Notably, in the majority of cases these upstream PAS were not found in annotated 3 0 UTRs but in other exons or introns. Recently, it was reported that CDK12 suppresses intronic polyadenylation sites [63]. While our data show up-regulation of intronic PAS, considering the much larger number of potential intronic PAS compared to exonic/UTR PAS, no particular enrichment of intronic PAS was observed among upstream up-regulated PAS.…”
Section: See Materials and Methods)contrasting
confidence: 71%
“…Notably, in contrast to the increase in distinctly positioned intronic polyadenylation events observed upon Cdk12 depletion 28 , we were unable to detect cleavage and polyadenylation at specific sites within gene bodies. We developed an algorithm to quantify sequencing reads with non-genomically encoded polyA tails that map to the distal polyA sites of genes.…”
Section: Resultscontrasting
confidence: 93%
“…Notably, changes in the distribution of the Ser2p signal upon CDK13 mel expression differed distinctly from those observed upon loss of a close paralog, CDK12. In cells lacking CDK12, Ser2p was strongly decreased across the gene body despite an increase in total RNAPII 28 . These data also suggest that CDK13 mel promotes oncogenesis via a mechanism that is distinct from CDK12.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Initiation of PROMPT and pre-mRNA transcription occurs at the edge of the nucleosome depleted region (NDR) in a bidirectional manner (Ntini et al, 2013;Andersson et al, 2014aAndersson et al, , 2014bDubbury et al, 2018) . Unlike pre-mRNAs, PROMPTs are rapidly degraded by the nuclear exosome (Preker et al, 2008) , a central player in RNA degradation.…”
Section: Introductionmentioning
confidence: 99%